Strain inhomogeneities in epitaxial BaFe2As2 thin films. Issue 11 (27th August 2015) - Chekhonin, Paul; Engelmann, Jan; Langer, Marco; Oertel, Carl‐Georg; Holzapfel, Bernhard; Skrotzki, Werner
Abstract : Epitaxial BaFe2 As2 thin films grown on spinel substrates with a thin iron buffer layer show strain‐induced superconductivity. Using high resolution electron backscatter diffraction in a scanning electron microscope very small orientation changes (≤ 0.2°) of the lattice and strain inhomogeneities on a length scale of few 100 nm or less were measured. Furthermore, partially strain relaxed areas were revealed. It was found, that the quality of the BaFe2 As2 thin films crucially depends on the iron buffer layer. Abstract : Epitaxial BaFe2 As2 thin films grown by pulsed laser deposition on spinel substrates with a thin iron buffer layer show strain‐induced superconductivity. Using high resolution electron backscatter diffraction in a scanning electron microscope very small orientation changes (≤ 0.2°) of the lattice and strain inhomogeneities on a length scale of few 100 nm or less were measured. Furthermore, partially strain relaxed areas were revealed. It was found, that the quality of the BaFe2 As2 thin films crucially depends on the iron buffer layer.